The Filtration Consolidation of an Elastic Porous Medium with Discontinuous Initial Conditions - F.M. Kadyrov; A.V. Kosterin (Учёные записки Казанского университета: Серия Физико-математические науки)
The problem of finding the initial conditions of consolidation for an elastic medium is solved in a general way; the Laplace equation is obtained for the water pressure. The problem of filtration consolidation for an infinite porous tube with circular symmetry is solved taking into account the found initial conditions: a solution for the pressure is described by the diffusion equation. If there is no ``hole'' at the origin of coordinates, then the water pressure becomes infinitely large.